Dot enzyme immunoassay: an alternative diagnostic aid for dengue fever and dengue haemorrhagic fever. - Cardosa, M. J. (World Health Organization, 1991)
A dot enzyme immunoassay (DEIA) for the detection of antibodies to dengue virus was tested for use as a tool in the presumptive diagnosis of dengue fever and dengue haemorrhagic fever. Paired sera from the following groups of patients were tested using the DEIA and the haemagglutination inhibition (HI) test: those with primary dengue fever; those experiencing a second dengue infection; and febrile patients who did not have dengue. The data obtained show that the DEIA can be effectively used at a serum dilution of 1:1000 to confirm presumptive recent dengue in patients with a second dengue infection. However, demonstration of seroconversion proved necessary for patients with primary dengue. At a serum dilution of 1:1000 the DEIA has a specificity of 97.3%. The role of this simple and rapid test in improving the effectivity of programmes for the control of dengue virus infection is discussed.